2017
DOI: 10.1080/15592324.2017.1300732
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyllide-a-Oxygenase (CAO) deficiency affects the levels of singlet oxygen and formation of plasmodesmata in leaves and shoot apical meristems of barley

Abstract: In plants, organogenesis and specification of cell layers and tissues rely on precise symplastic delivery of regulatory molecules via plasmodesmata. Accordingly, abundance and aperture of plasmodesmata at individual cell boundaries should be controlled by the plant. Recently, studies in Arabidopsis established reactive oxygen species as major regulators of plasmodesmata formation and gating. We show that in a barley mutant deficient in the synthesis of chlorophyll b, the numbers of plasmodesmata in leaves and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Different letters indicate significant differences at p < 0.05 according to one-way ANOVA with post hoc Tukey's test. Data for barley are reproduced from Dmitrieva et al ( 2017 ). Micrographs show PD in one of the Solanum tuberosum apices examined.…”
Section: Resultsmentioning
confidence: 99%
“…Different letters indicate significant differences at p < 0.05 according to one-way ANOVA with post hoc Tukey's test. Data for barley are reproduced from Dmitrieva et al ( 2017 ). Micrographs show PD in one of the Solanum tuberosum apices examined.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that sucrose-sensitive developmental process of rfc3 can be traced back to primary root growth rather than to LR developmental processes ( Horiguchi et al, 2003 ). Although how plastid function ensures LR development should be investigated in a future study, it is interesting to note that plastid function (or dysfunction) influences symplasmic communication and spatial organization of the root apical meristem ( Benitez-Alfonso et al, 2009 ; Burch-Smith et al, 2011 ; Stonebloom et al, 2012 ; Dmitrieva et al, 2017 ). The intercellular movement of key transcription factors, such as SHORT ROOT (SHR) and WOX5 ( Nakajima et al, 2001 ; Pi et al, 2015 ), and symplasmic communication in the stem cell niche ( Liu et al, 2017 ), are crucial for establishing and maintaining the root apical meristem.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, a buffered SOSG solution with a final concentration of 5-100 µM is introduced into leaves or seedlings by means of vacuum-infiltration [94,125]. SOSG was described as not being able to penetrate cell membranes [126]; however, other authors reported that in high concentrations, SOSG can enter cells and accumulate in the nucleus [121,122].…”
Section: Detection Of 1 O 2 In Plantsmentioning
confidence: 99%